Design and development of an autonomous maze solving robot (micromouse) Part 1 - Lai, Gilbert Vui Hao (2011)
Autonomous robots are popular nowadays, its exist almost everywhere around the world. An autonomous robots which have the ability to solve maze, can also be used for other applications such as the robots which will be able to deliver medicine to the patient in the hospital, to rescue victims from disaster scene. The main purpose of this project is to design and develop an autonomous maze solving robots which will also known as Micromouse in this project. Actel’s FPGAs and Silicon Labs’ Microcontroller C8051 will be focused in this project as these two ICs will act as the brain of the Micromouse and interact with the peripheral devices. VHDL editing and simulation will be done using the Libero IDE v9.0. VHDL designs such as address decoder, filter AB which is also known as quadrature decoder, 32bits unsigned up/down counter, PWM, mux output is to produce the desired output to the C8051 from the 32 bits counter and bi-directional buffer. Besides that, a user friendly GUI will also be created to enable the user to tune the Micromouse easily instead of using Hyperterminal. The GUI will be developed using Visual Basic 2010 and the GUI will include 4 tuning sections such as SENSOR, MOTOR CONSTANT, NORMAL TURN and DASH. The mentioned section is required to tune by the user so that the Micromouse can perform smoothly. Further research will be done in order to complete this project.